Factors influencing response to neoadjuvant chemoradiation and outcomes in rectal cancer patients: tertiary Indian cancer hospital experience - Engineer, Reena; Basu, Trinanjan; Chopra, Supriya; Arya, Supreeta; Patil, Prachi; Mehta, Shaesta; Ramadwar, Mukta; Deodhar, Kedar; Shrivastava, Shyam Kishore (Journal of Gastrointestinal Oncology; Vol 6, No 2 (April 13, 2015): Journal of Gastrointestinal Oncology, 2015)
Background: In the treatment of rectal cancers several randomized trials have demonstrated benefits of neoadjuvant chemoradiotherapy (NACRT) in downstaging as well as survival among these patients. We investigated the patient and tumor related variables dictating the outcomes in these patients. Methods: Biopsy proven treatment naive 182 rectal cancer patients underwent NACRT from June 2006 to December 2010. The entire patients received long course conventionally fractionated external beam radiotherapy with concurrent oral Capecitabine. At 6 weeks from completion of NACRT clinicoradiological assessment was carried out for surgical feasibility. All patients were given postoperative adjuvant chemotherapy either single agent or multi drug regimen depending upon biopsy report. Results: Among 182 patients, 131 (72%) underwent surgery and initial T stage and signet ring cell morphology were major determinant of operability. Among the 131 operated patients at median follow up of 36 months, 94 (72%) are alive and disease free. With a median follow up of 42 months the 5-year disease free survival (DFS) and overall survival (OS) was 60% and 77%. The majority of the failures were distal but with more advanced disease at presentation both local and distal failures were similar. While assessing survival by multivariate analysis patients having positive nodes post-surgery had a significantly poorer DFS (P=0.001), while signet ring cell morphology and pre-treatment carcino-embryonic antigen (CEA) levels strongly influenced OS (P=0.03). Conclusions: The outcome of our patients were similar to World Literature and signet ring cell morphology, pre-treatment CEA level, and pathological nodal staging all were influential in determining survival. Besides this, the study also highlights the fact that tumours with signet ring cell morphology appearing in younger population with poor survival needs prospective evaluation for more intense CRT regimen and aggressive surgical resections.